1 / 60

640 likes | 889 Vues

11.5 = Recursion & Iteration. Arithmetic = adding (positive or negative). Arithmetic = adding (positive or negative) 3, 6, 9, 12, …. Arithmetic = adding (positive or negative) 3, 6, 9, 12, … d = 3. Arithmetic = adding (positive or negative) 3, 6, 9, 12, … d = 3

Télécharger la présentation
## 11.5 = Recursion & Iteration

**An Image/Link below is provided (as is) to download presentation**
Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.
Content is provided to you AS IS for your information and personal use only.
Download presentation by click this link.
While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.
During download, if you can't get a presentation, the file might be deleted by the publisher.

E N D

**Arithmetic = adding (positive or negative)**3, 6, 9, 12, …**Arithmetic = adding (positive or negative)**3, 6, 9, 12, … d = 3**Arithmetic = adding (positive or negative)**3, 6, 9, 12, … d = 3 *Formula for the nth term based on a1 and d. an = a1+(n–1)d**Arithmetic = adding (positive or negative)**3, 6, 9, 12, … d = 3 *Formula for the nth term based on a1 and d. an = a1+(n–1)d Geometric = multiplying (#’s > 1 or #’s < 1)**Arithmetic = adding (positive or negative)**3, 6, 9, 12, … d = 3 *Formula for the nth term based on a1 and d. an = a1+(n–1)d Geometric = multiplying (#’s > 1 or #’s < 1) 2, 10, 50, 250, …**Arithmetic = adding (positive or negative)**3, 6, 9, 12, … d = 3 *Formula for the nth term based on a1 and d. an = a1+(n–1)d Geometric = multiplying (#’s > 1 or #’s < 1) 2, 10, 50, 250, … r = 5**Arithmetic = adding (positive or negative)**3, 6, 9, 12, … d = 3 *Formula for the nth term based on a1 and d. an = a1+(n–1)d Geometric = multiplying (#’s > 1 or #’s < 1) 2, 10, 50, 250, … r = 5 *Formula for the nth term based on a1 and r. an = a1r(n – 1)**Arithmetic = adding (positive or negative)**3, 6, 9, 12, … d = 3 *Formula for the nth term based on a1 and d. an = a1+(n–1)d Geometric = multiplying (#’s > 1 or #’s < 1) 2, 10, 50, 250, … r = 5 *Formula for the nth term based on a1 and r. an = a1r(n – 1) Recursion = formula-based (“neither”)**Arithmetic = adding (positive or negative)**3, 6, 9, 12, … d = 3 *Formula for the nth term based on a1 and d. an = a1+(n–1)d Geometric = multiplying (#’s > 1 or #’s < 1) 2, 10, 50, 250, … r = 5 *Formula for the nth term based on a1 and r. an = a1r(n – 1) Recursion = formula-based (“neither”) 2, 4, 16, 256, …**Arithmetic = adding (positive or negative)**3, 6, 9, 12, … d = 3 *Formula for the nth term based on a1 and d. an = a1+(n–1)d Geometric = multiplying (#’s > 1 or #’s < 1) 2, 10, 50, 250, … r = 5 *Formula for the nth term based on a1 and r. an = a1r(n – 1) Recursion = formula-based (“neither”) 2, 4, 16, 256, … -The pattern is that you’re squaring each previous term.**Arithmetic = adding (positive or negative)**3, 6, 9, 12, … d = 3 *Formula for the nth term based on a1 and d. an = a1+(n–1)d Geometric = multiplying (#’s > 1 or #’s < 1) 2, 10, 50, 250, … r = 5 *Formula for the nth term based on a1 and r. an = a1r(n – 1) Recursion = formula-based (“neither”) 2, 4, 16, 256, … -The pattern is that you’re squaring each previous term. an+1 = (an)2**Recursion = formula-based (“neither”)**2, 4, 16, 256, … -The pattern is that you’re squaring each previous term. an+1 = (an)2 *Note that this formula only applies to this particular example!!!**Recursion = formula-based (“neither”)**2, 4, 16, 256, … -The pattern is that you’re squaring each previous term. an+1 = (an)2 *Note that this formula only applies to this particular example!!! Basic Formula: next term = #(1stterm)# ± #**Recursion = formula-based (“neither”)**2, 4, 16, 256, … -The pattern is that you’re squaring each previous term. an+1 = (an)2 *Note that this formula only applies to this particular example!!! Basic Formula: next term = #(1stterm)# ± # **The #’s are possibilities, but not requirements.**Recursion = formula-based (“neither”)**2, 4, 16, 256, … -The pattern is that you’re squaring each previous term. an+1 = (an)2 *Note that this formula only applies to this particular example!!! Basic Formula: next term = #(1stterm)# ± # **The #’s are possibilities, but not requirements. Exs. an = 3an-1 + 4 an+1 = (an)2 – 9 an+2 = 2an – an+1**Ex. 1 Find the first five terms of each sequence.**a1 = 10, an+1 = 4an + 1**Ex. 1 Find the first five terms of each sequence.**a1 = 10, an+1 = 4an + 1 a1 = 10**Ex. 1 Find the first five terms of each sequence.**a1 = 10, an+1 = 4an + 1 a1 = 10 a1+1 = 4a1 + 1**Ex. 1 Find the first five terms of each sequence.**a1 = 10, an+1 = 4an + 1 a1 = 10 a1+1 = 4a1 + 1 = 4(10) + 1**Ex. 1 Find the first five terms of each sequence.**a1 = 10, an+1 = 4an + 1 a1 = 10 a1+1 = 4a1 + 1 = 4(10) + 1 = 41**Ex. 1 Find the first five terms of each sequence.**a1 = 10, an+1 = 4an + 1 a1 = 10 a1+1 = 4a1 + 1 = 4(10) + 1 = 41 a2 = 41**Ex. 1 Find the first five terms of each sequence.**a1 = 10, an+1 = 4an + 1 a1 = 10 a1+1 = 4a1 + 1 = 4(10) + 1 = 41 a2 = 41 a2+1 = 4a2 + 1**Ex. 1 Find the first five terms of each sequence.**a1 = 10, an+1 = 4an + 1 a1 = 10 a1+1 = 4a1 + 1 = 4(10) + 1 = 41 a2 = 41 a2+1 = 4a2 + 1 = 4(41) + 1**Ex. 1 Find the first five terms of each sequence.**a1 = 10, an+1 = 4an + 1 a1 = 10 a1+1 = 4a1 + 1 = 4(10) + 1 = 41 a2 = 41 a2+1 = 4a2 + 1 = 4(41) + 1 = 165**Ex. 1 Find the first five terms of each sequence.**a1 = 10, an+1 = 4an + 1 a1 = 10 a1+1 = 4a1 + 1 = 4(10) + 1 = 41 a2 = 41 a2+1 = 4a2 + 1 = 4(41) + 1 = 165 a3 = 165**Ex. 1 Find the first five terms of each sequence.**a1 = 10, an+1 = 4an + 1 a1 = 10 a1+1 = 4a1 + 1 = 4(10) + 1 = 41 a2 = 41 a2+1 = 4a2 + 1 = 4(41) + 1 = 165 a3 = 165 a3+1 = 4a3 + 1**Ex. 1 Find the first five terms of each sequence.**a1 = 10, an+1 = 4an + 1 a1 = 10 a1+1 = 4a1 + 1 = 4(10) + 1 = 41 a2 = 41 a2+1 = 4a2 + 1 = 4(41) + 1 = 165 a3 = 165 a3+1 = 4a3 + 1 = 4(165) + 1**Ex. 1 Find the first five terms of each sequence.**a1 = 10, an+1 = 4an + 1 a1 = 10 a1+1 = 4a1 + 1 = 4(10) + 1 = 41 a2 = 41 a2+1 = 4a2 + 1 = 4(41) + 1 = 165 a3 = 165 a3+1 = 4a3 + 1 = 4(165) + 1 = 661**Ex. 1 Find the first five terms of each sequence.**a1 = 10, an+1 = 4an + 1 a1 = 10 a1+1 = 4a1 + 1 = 4(10) + 1 = 41 a2 = 41 a2+1 = 4a2 + 1 = 4(41) + 1 = 165 a3 = 165 a3+1 = 4a3 + 1 = 4(165) + 1 = 661 a4 = 661**Ex. 1 Find the first five terms of each sequence.**a1 = 10, an+1 = 4an + 1 a1 = 10 a1+1 = 4a1 + 1 = 4(10) + 1 = 41 a2 = 41 a2+1 = 4a2 + 1 = 4(41) + 1 = 165 a3 = 165 a3+1 = 4a3 + 1 = 4(165) + 1 = 661 a4 = 661 a4+1 = 4a4 + 1**Ex. 1 Find the first five terms of each sequence.**a1 = 10, an+1 = 4an + 1 a1 = 10 a1+1 = 4a1 + 1 = 4(10) + 1 = 41 a2 = 41 a2+1 = 4a2 + 1 = 4(41) + 1 = 165 a3 = 165 a3+1 = 4a3 + 1 = 4(165) + 1 = 661 a4 = 661 a4+1 = 4a4 + 1 = 4(661) + 1**Ex. 1 Find the first five terms of each sequence.**a1 = 10, an+1 = 4an + 1 a1 = 10 a1+1 = 4a1 + 1 = 4(10) + 1 = 41 a2 = 41 a2+1 = 4a2 + 1 = 4(41) + 1 = 165 a3 = 165 a3+1 = 4a3 + 1 = 4(165) + 1 = 661 a4 = 661 a4+1 = 4a4 + 1 = 4(661) + 1 = 2645**Ex. 1 Find the first five terms of each sequence.**a1 = 10, an+1 = 4an + 1 a1 = 10 a1+1 = 4a1 + 1 = 4(10) + 1 = 41 a2 = 41 a2+1 = 4a2 + 1 = 4(41) + 1 = 165 a3 = 165 a3+1 = 4a3 + 1 = 4(165) + 1 = 661 a4 = 661 a4+1 = 4a4 + 1 = 4(661) + 1 = 2645 a5 = 2645**Ex. 1 Find the first five terms of each sequence.**a1 = 10, an+1 = 4an + 1 a1 = 10 a1+1 = 4a1 + 1 = 4(10) + 1 = 41 a2 = 41 a2+1 = 4a2 + 1 = 4(41) + 1 = 165 a3 = 165 a3+1 = 4a3 + 1 = 4(165) + 1 = 661 a4 = 661 a4+1 = 4a4 + 1 = 4(661) + 1 = 2645 a5 = 2645**Ex. 2Write a recursive formula for the sequence.**16, 10, 7, 5.5, 4.75**Ex. 2 Write a recursive formula for the sequence.**16 10 7 5.5 4.75 -6 -3 -1.5 -0.75**Ex. 2 Write a recursive formula for the sequence.**16 10 7 5.5 4.75 -6 -3 -1.5 -0.75 *Each difference is half the previous difference!**Ex. 2 Write a recursive formula for the sequence.**16 10 7 5.5 4.75 -6 -3 -1.5 -0.75 *Each difference is half the previous difference! a1 = 16**Ex. 2 Write a recursive formula for the sequence.**16 10 7 5.5 4.75 -6 -3 -1.5 -0.75 *Each difference is half the previous difference! a1 = 16 a2 = 0.5(16) ± ? = 10**Ex. 2 Write a recursive formula for the sequence.**16 10 7 5.5 4.75 -6 -3 -1.5 -0.75 *Each difference is half the previous difference! a1 = 16 a2 = 0.5(16) ± ? = 10 8 ± ? = 10**Ex. 2 Write a recursive formula for the sequence.**16 10 7 5.5 4.75 -6 -3 -1.5 -0.75 *Each difference is half the previous difference! a1 = 16 a2 = 0.5(16) ± ? = 10 8 ± ? = 10 a3 = 0.5(10) ± ? = 7**Ex. 2 Write a recursive formula for the sequence.**16 10 7 5.5 4.75 -6 -3 -1.5 -0.75 *Each difference is half the previous difference! a1 = 16 a2 = 0.5(16) ± ? = 10 8 ± ? = 10 a3 = 0.5(10) ± ? = 7 5 ± ? = 7**Ex. 2 Write a recursive formula for the sequence.**16 10 7 5.5 4.75 -6 -3 -1.5 -0.75 *Each difference is half the previous difference! a1 = 16 a2 = 0.5(16) ± ? = 10 8 ± ? = 10 a3 = 0.5(10) ± ? = 7 5 ± ? = 7 a4 = 0.5(7) ± ? = 5.5**Ex. 2 Write a recursive formula for the sequence.**16 10 7 5.5 4.75 -6 -3 -1.5 -0.75 *Each difference is half the previous difference! a1 = 16 a2 = 0.5(16) ± ? = 10 8 ± ? = 10 a3 = 0.5(10) ± ? = 7 5 ± ? = 7 a4 = 0.5(7) ± ? = 5.5 3.5 ± ? = 5.5**Ex. 2 Write a recursive formula for the sequence.**16 10 7 5.5 4.75 -6 -3 -1.5 -0.75 *Each difference is half the previous difference! a1 = 16 a2 = 0.5(16) ± ? = 10 8 ± ? = 10 a3 = 0.5(10) ± ? = 7 5 ± ? = 7 a4 = 0.5(7) ± ? = 5.5 3.5 ± ? = 5.5 a5 = 0.5(5.5) ± ? = 4.75**Ex. 2 Write a recursive formula for the sequence.**16 10 7 5.5 4.75 -6 -3 -1.5 -0.75 *Each difference is half the previous difference! a1 = 16 a2 = 0.5(16) ± ? = 10 8 ± ? = 10 a3 = 0.5(10) ± ? = 7 5 ± ? = 7 a4 = 0.5(7) ± ? = 5.5 3.5 ± ? = 5.5 a5 = 0.5(5.5) ± ? = 4.75 2.75 ± ? = 4.75**Ex. 2 Write a recursive formula for the sequence.**16 10 7 5.5 4.75 -6 -3 -1.5 -0.75 *Each difference is half the previous difference! a1 = 16 a2 = 0.5(16) ± ? = 10 8 ± 2 = 10 a3 = 0.5(10) ± ? = 7 5 ± 2 = 7 a4 = 0.5(7) ± ? = 5.5 3.5 ± 2 = 5.5 a5 = 0.5(5.5) ± ? = 4.75 2.75 ± 2 = 4.75**Ex. 2 Write a recursive formula for the sequence.**16 10 7 5.5 4.75 -6 -3 -1.5 -0.75 *Each difference is half the previous difference! a1 = 16 a2 = 0.5(16) ± ? = 10 8 ± 2= 10 a3 = 0.5(10) ± ? = 7 5 ± 2 = 7 a4 = 0.5(7) ± ? = 5.5 3.5 ± 2 = 5.5 a5 = 0.5(5.5) ± ? = 4.75 2.75 ± 2 = 4.75 So an+1 = 0.5an + 2

More Related